2007
DOI: 10.1177/070674370705200109
|View full text |Cite
|
Sign up to set email alerts
|

An Outcome Measure in Schizophrenia: Mortality

Abstract: Objective: To determine the current outcome of schizophrenia, with mortality rate as the outcome measure. Method: Recent health, suicide, victim of violence, and mortality statistics were reviewed. Results: The general health of individuals with schizophrenia suffers from neglect, poor life style choices, and current treatments that increase death rates. Conclusion: Mortality in schizophrenia is rising, and it is the responsibility of physicians and health care planners to intervene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…One exception is China, where the suicide rates for men and women are equal, or even higher for women [90]. In general, the suicide rate is approximately three-to four-times higher for men than for women [45,[90][91][92]. The gender difference seems to be less marked among patients with schizophrenia.…”
Section: Gender and Suicide Risk In Schizophreniamentioning
confidence: 97%
See 1 more Smart Citation
“…One exception is China, where the suicide rates for men and women are equal, or even higher for women [90]. In general, the suicide rate is approximately three-to four-times higher for men than for women [45,[90][91][92]. The gender difference seems to be less marked among patients with schizophrenia.…”
Section: Gender and Suicide Risk In Schizophreniamentioning
confidence: 97%
“…During the last few decades there have been changes in health systems, with significant reductions in in-patient capacity. These changes have been suspected to be an important factor in the rising mortality seen in patients with schizophrenia [44,45]. However, the effect of the reduction in in-patient capacity on the suicide rate remains unclear due to conflicting results [46].…”
Section: Reviewmentioning
confidence: 99%
“…Mortality is increasingly recognized as a crucial outcome measure for quality of care patients with schizophrenia receive [2,3]. Several studies reported that people with schizophrenia live shorter lives compared with the general population [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among these metabolic syndrome, already a concern in persons with schizophrenia based on life style risk factors, is a major concern with drugs that cause increased body mass index, hyperlipidemia, reduced insulin sensitivity, and are associated with an increased incidence of diabetes. Reduction in life span is great, and expected to worsen with increased exposure to pharmacological adverse effects (Hennekens et al, 2005;Auquier et al, 2006;Seeman, 2007;Colton and Manderscheid, 2006;Newcomer and Hennekens, 2007). In most respects, drug development for schizophrenia has not progressed appreciably since the introduction of chlorpromazine, a point which recently found emphasis in a large first episode clinical trial in Beijing comparing the original antipsychotic drug, chlorpromazine, with the only second generation drug with documented superiority, clozapine.…”
Section: Introductionmentioning
confidence: 99%